ANALISIS KENDALA YANG DIHADAPI NELAYAN DALAM MENINGKATKAN PRODUKSI IKAN LAUT DIPESISIR PANTAI AMPENAN KECAMATAN AMPENAN KOTA MATARAM - Rd Tuty Sariwulan (Fakultas Ekonomi Universitas Negeri Jakarta, 2010)
ABSTRACTThe aim study is to determine the constraints faced by fishermen in an attempt to increase marine fish production. The study was descriptive research using primary data collected from 20 respondents fishermen. Data collected were analyzed using tabulation or frequency analysis. The results showed that the constraints faced by fishermen obtained from a study of 20 respondents is as follows: equipment constraints as many as 14 respondents (70%). Capital constraints 8 respondents (40%) and the constraints of natural conditions a orang respondents (5%). While other constraints obtained the results of discussions with 20 people of respondents is the lack of constraint in writing regulations governing the location of fishing among anglers fishing with the fishermen penjaring so often the case a misunderstanding, then constraint relief boat model boat which does not comply with the condition of marine / aquatic fishing where the fishermen village of North Ampenan.Keywords: fisherman, marine fish production, descriptive research